Influence of Medication on Flare Up and Infection After Elective Orthopedic Surgery in Rheumatoid Arthritis Patient – A Narrative Review - Yaldi Rosadi; Yustin Marinta; Muthiah Nur Afifah (Journal Orthopaedi and Traumatology Surabaya)
Background: Orthopedic Surgery in Rheumatoid Arthritis (RA) patients is still controversial between orthopedic surgeons and rheumatologists, mainly due to infection and disease flares. The incidence of postoperative infections may be high due to the immunosuppressive effect of RA medication. Conversely, discontinuance of antirheumatic agents increases the possibility of a disease flare. The objective of our review is to assess the influence of drugs on both incidences. Literature Review: There were 13 studies included in this review. Methotrexate (MTX) is the most common csDMARD option among the included studies. One retrospective study that the incidence of flares tends to be higher among the group of patients who received MTX therapy and stopped more than one week before surgery than the group who did not stop. The use of MTX doses of 5 to 10 mg/week did not show an association with infection or flare incidence. On the use of bDMARD, 37.0% of patients had higher surgical site infection (SSI). Specifically, Tumor Necrosis Factor-alpha (TNF-α) inhibitors significantly (OR: 9.5, 95% CI: 1.0-88.8) increase the incidence of postoperative infections in standard-dose and high-dose, but not significantly in the rate of flares. Summary: csDMARD is recommended for continuous therapy, whereas for bDMARD, although it is recommended for withholding in the perioperative period, the results of the study did not show significant differences. The ideal dosage of medication is by the basic properties of the drug. In comparison, the incidence of flares and infections was significantly higher in biologic than csDMARD.